2021
DOI: 10.3390/molecules26040905
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Phytochemical Screening of Different Organs of Calotropis procera and the Ovicidal Effect of Their Extracts to the Foodstuff Pest Cadra cautella

Abstract: In developing countries, crop deterioration is mainly caused by inappropriate storage conditions that promote insect infestation. Synthetic pesticides are associated with serious adverse effects on humans and the environment. Thus, finding alternative “green” insecticides is a very pressing need. Calotropis procera (Aiton) Dryand (Apocynaceae) growing in Saudi Arabia was selected for this purpose. LC-MS/MS analysis was applied to investigate the metabolic composition of different C. procera extracts. Particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Finally, in a recent study it was found that extracts of Calotripis procera roots displayed the most potent activity, with 50% of E. cautella Walker eggs not hatching at 10.000 ppm (1%). The chemical composition analysis of the extracts demonstrated a high presence of cardenolides, including calactin, uscharidin, 15β-hydroxy-calactin, 16β-hydroxy-calactin and 12β-hydroxy-calactin [162]. When five Eucalyptus species, namely, E. camaldulensis, E. astringens, E. leucoxylon, E. lehmannii and E. rudis, were assessed for their fumigant activity on Ephestia spp., the E. camaldulensis essential oil was more toxic against E. cautella and Ephestia kuehniella Zeller and the LC 50 values were 11.07 and 26.73 µL/L air, respectively.…”
Section: Butterflies and Moths (Lepidoptera)mentioning
confidence: 99%
“…Finally, in a recent study it was found that extracts of Calotripis procera roots displayed the most potent activity, with 50% of E. cautella Walker eggs not hatching at 10.000 ppm (1%). The chemical composition analysis of the extracts demonstrated a high presence of cardenolides, including calactin, uscharidin, 15β-hydroxy-calactin, 16β-hydroxy-calactin and 12β-hydroxy-calactin [162]. When five Eucalyptus species, namely, E. camaldulensis, E. astringens, E. leucoxylon, E. lehmannii and E. rudis, were assessed for their fumigant activity on Ephestia spp., the E. camaldulensis essential oil was more toxic against E. cautella and Ephestia kuehniella Zeller and the LC 50 values were 11.07 and 26.73 µL/L air, respectively.…”
Section: Butterflies and Moths (Lepidoptera)mentioning
confidence: 99%
“…Calotropis procera is known to possess various medicinal properties, rarely known for its toxicity. All parts of C.procera are reputed to be toxic to humans, cattle, sheep, rabbits, and rats, may die from C. procera poisoning, bactericidal, larvicidal and cytotoxic effects [37,38]. Although the latex of C. procera is known to possess various medicinal properties, it is rarely known for its toxicity.…”
Section: Toxicity Activitymentioning
confidence: 99%
“…More recently, the ovicidal effect of extracts of Calotropis procera to the Pest Cadra cautella. The extracts displayed a good activity with 50% of C. cautella eggs not hatching at 10.000 ppm (1%) [24]. Recently, [25] have estimated the biological activity of plant extracts on the small tomato borer Neoleucinodes elegantalis.…”
Section: Introductionmentioning
confidence: 99%